(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Transgender, Intersex, Homosexual, Gay, Bisexual, Kinnar, Hijra, and Queer categories include LGBT. The current article aims to investigate the Socio-Legal Impacts of Section 377 (Indian Penal Code, 1860) on Indian SocietyAn Overview – As purely non-doctrinal research on the above topic is not possible as a broad view of the subject will be required to justify the contentions in this regard so the doctrinal approach would be included in this study. The libraries of the Indian Law Institute and the University of Delhi, the Jodhpur National Law University and the University of Rajasthan provide adequate access to the related material to be used in this analysis by the researcher. The Review of Commission Reports, Supreme Court decisions, International Bodies, Websites, Primary Source – Legislative Materials, Government Records and Secondary Source Reports – Text Books, Periodicals, Indian Law Journals were reviewed and referred in the course of Research Work therefore the research methodology adopted will be doctrinal. Homosexuals are not welcomed in family and society. They are not even regarded as normal human beings. If homosexual or gay people remain together, this is deemed against the law. This minority has faced social inequality in society. In 1862 the British parliament passed a law banning such actions for the good of society. The LGBT community began fighting this injustice done to them in 2014 and eventually, this so-called unnatural conduct was decriminalised under Section 377 on 6th September 2018. After the decriminalization of Section 377. The positives of this judgement are that it will provide social, economic and educational empowerment of transgenders. It prohibits discrimination against transgender person and awards right to residence in his her household. There is provision of healthcare facilities, rehabilitation for them. They will be awarded Certificate of identity but this creates a room for negatives for above said Bill. The biggest drawback is the requisite of a screening Committee to certify their status. There is a surgery clause, which is unjust. LGBT are not given any reservations although they are a minority who have been illtreated both emotionally and financially, since time immemorial.